2022
DOI: 10.1007/s00520-022-07389-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise interventions on cancer-related fatigue in breast cancer patients: an overview of systematic reviews

Abstract: Objective This overview of systematic reviews aims to critically appraise and consolidate evidence from current systematic reviews (SRs)/meta-analyses on the effects of exercise interventions on cancer-related fatigue (CRF) in breast cancer patients. Methods SRs/meta-analyses that explored the effects of exercise interventions on CRF in breast cancer patients compared with the routine methods of treatment and care were retrieved from nine databases. The me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 78 publications
2
2
0
Order By: Relevance
“…In contrast, both groups improved their strength performance after a three-week combined strength and mobility training on FIVE® devices, respectively device-supported training. Because of the specificity of the two approaches, these results are in accordance with our initial theoretical assumptions, and they support and complement previous results concerning aerobic capacity, lower and upper limb strength, and agility [ 26 , 27 , 29 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, both groups improved their strength performance after a three-week combined strength and mobility training on FIVE® devices, respectively device-supported training. Because of the specificity of the two approaches, these results are in accordance with our initial theoretical assumptions, and they support and complement previous results concerning aerobic capacity, lower and upper limb strength, and agility [ 26 , 27 , 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies examined the effects of aerobic and resistance training in breast cancer patients, but did not analyze the results of a combined mobility and resistance training on devices in breast cancer patients in rehabilitation [ 25 , 26 ]. Apart from that, the implementation of FIVE® devices in exercise therapy has not been investigated for patients in breast cancer rehabilitation yet [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings of the poor methodological quality of SRs in the food field are in line with those from assessments of the methodological quality of SRs that used the AMSTAR 2 tool in other fields, including acupuncture [16,17], dentistry [18], Tai Chi [19,20], surgery [21,22], major depression in adults [23], chronic obstructive pulmonary disease [24], cardiovascular risk [25], physical activity [26], pancreatic cancer [27], chronic heart failure [28], cancerrelated fatigue [29], Alzheimer's disease [30], chronic spinal pain [31], neonatal pain [32], hip fractures [33], and atopic eczema [34]. Although the target patients or participants and interventions in those studies differed between each study, all demonstrated that the majority of SRs included had low methodological quality ("low" or "critically low").…”
Section: Findings In Contextsupporting
confidence: 82%
“…PA has been suggested as a possible intervention to enhance the quality of life of women with breast cancer both pre-and postdiagnosis, and after surgery [13]. Exercise can help women with breast cancer and survivors improve their quality of life, cardiorespiratory tness, physical functioning, and tiredness [14]. PA may also increase overall and disease-free recovery in women with breast cancer as exercise can help women with breast cancer and survivors improve their quality of life, cardiorespiratory tness, physical functioning, and tiredness well as reduce breast cancer recurrence and improve quality of life in women with breast cancer postmastectomy.…”
Section: Introductionmentioning
confidence: 99%